The psychological profiles of ex-prisoner torture survivors who served in Diyarbakır prison between the years of 1980-1984 - Arslan, Sevda (İstanbul Bilgi Üniversitesi, 2011)
[Abstract Not Available]
1980-1984 yılları arasında Diyarbakır cezaevinde bulunmuş eski mahkum işkence mağdurlarının psikolojik profilleri